Mixed Ligand Complexes of Pb(II) Chelates of Some Organic Acids with Picolinic Acid-N-Oxide and Quinaldinic Acid-N-Oxide - Prakash, Dharam; K. Gupta, Anju; K. Sharma, D.; Kumar Sinha, Arun (Asian Journal of Chemistry, 2010)
The mixed ligand complexes of the type ML2·HL', where M = Pb, HL' = picolinic acid-N-oxide, HH = o-nitrophenol(ONP), 2,4-dinitrophenol (DNP) and 2,4,6-trinitrophenol (TNP) have been synthesised and characterised by physical measurements. IR spectral data show that hydrogen bonding in these complexes is a dominent factor for their stability.